Urbanização litorânea e planejamento na metrópole: a produção do espaço urbano de Fortaleza - Cunha, Gabriela Bento (2017)
In the second half of the twentieth century, Northeastern cities have undergone changes, politic, economic and social order. This process is linked to factors such as development polities, enhancement of beach areas, coastal urbanization and the metropolises of space. Thus, it is understood that the Brazilian Northeast is today a consolidated region through a redefinition of their roles and their space. If before, the loaded stigma was a "problem area" today, reflects the wealth of a multifunctional space: agribusiness, tourism, and technological center. In this context, this study seeks to understand how planning and metropolization space corroborate the coastal urbanization of Fortaleza and its metropolitan region. It is understood that the advance of metropolises in the Northeast is associated with the consolidation of tourism and modern maritime vilegiatura and its consequences. You can understand the changes on the coast of the Northeast metropolises through the process of urbanization and reproduction of urban linked to leisure practices. In Ceará, this process is diffused by the primate city - the capital Fortaleza - and its periurban municipalities. The transformation of the city in the metropolis and the overflow of the leisure relationships are the result of a focused planning for tourism and expansion of the urban fabric. Fortaleza incorporates today, the role of one of the most important cities of the country. This logic is made possible mainly by economic activities encompassed in Fortaleza, especially tourism and modern maritime vilegiatura practiced by increasing fractions of society. The practices associated with leisure dynamics are of paramount importance in the coastal urbanization phenomenon, the valuation of the beach bands and the expansion of the urban fabric. If before the beach areas represented the place of the lower classes, the demand for leisure and attraction by the sea becomes a valued space and enormous changes. Maritime vilegiatura and coastal tourism, with the desire to live on the beach, foster a dispersed urbanization, fragmented and also the (re) production of urban space, expanding into periurban municipalities of Fortaleza: Caucaia and Aquiraz. Based on these studies, we analyze how modern maritime practices and actions of public and private planning contribute to coastal urbanization of the city and the composition of their morphology.